PRINSIP KESANTUNAN BERBAHASA DALAM TINDAK TUTUR PEGAWAI DAN NASABAH BANK SUMSEL BABEL - Suciati, Niken; Murniviyanti, Liza; Nufus, Hayatun (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2022)
The purpose of this study is to identify and explain the principles of politeness in speech behavior of employees and customers of Bank Sumsel Babel, a sub-branch of Keluang of Musi Banyuasin Regency. Research by descriptive qualitative methods. The method of data collection in this study is observation, record, record. Data analysis techniques were performed by translating and analyzing the recorded data into written form. Among the findings on employee and customer speech behavior in business interactions is the principle of politeness in speech, which is governed by the maxim of wisdom and the maxim of generosity.